Intention of Rationality in the Research Practice of Central Asian Thinkers - Kushakov Shuxrat Saliyevich (Peerian Journals Publishing, 2022)
the paper considers the use of the norms of scientific rationality in the research practice of Central Asian thinkers during the first wave of the socio-cultural Renaissance (VIIIIX centuries). The scientific and logical-methodological ideas of thinkers (Beruni and Ibn Sina) concerning the nature of scientific knowledge, norms and principles of scientific rationality are analysed: objectivity, problematic, causality.
Keywords: science; rationality; norm; truth